2021
DOI: 10.1016/j.ejvs.2021.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Decrease in Mortality from Abdominal Aortic Aneurysms (2001 to 2015): Is it Decreasing Even Faster?

Abstract: The early 21st century has witnessed a global decrease in mortality from abdominal aortic aneurysms (AAA) which was associated with variations in the global prevalence of cardiovascular risk factors. This study investigates whether these trends continued into the second decade of the 21st century.Objective: The early twenty first century witnessed a decrease in mortality from abdominal aortic aneurysms (AAA), which was associated with variations in the prevalence of cardiovascular risk factors. This study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The rise and fall of AAA-related mortality rates in developed countries correlate strongly with the changes in smoking prevalence [ 11 , 15 ]. Notably, AAA mortality in men is declining in many countries, particularly in the United States, the United Kingdom, and the Netherlands, while it seems to be on the rise among men and women in Hungary, Romania, and Japan [ 22 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The rise and fall of AAA-related mortality rates in developed countries correlate strongly with the changes in smoking prevalence [ 11 , 15 ]. Notably, AAA mortality in men is declining in many countries, particularly in the United States, the United Kingdom, and the Netherlands, while it seems to be on the rise among men and women in Hungary, Romania, and Japan [ 22 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…However, our study suggests that AA-related mortality has increased in the recent three years and will continue increasing in the future. A study of trends in mortality from abdominal aortic aneurysms covering 17 countries showed an accelerating downward trend in mortality from abdominal aortic aneurysms as of 2015, but this study included fewer countries and mainly developed countries [ 20 ]. A Swedish population-based screening study observed a steady increase in the incidence of AAA among older men aged 65–99 years up to 2010, but they attributed the increase in the rate of diagnostic testing rather than a true increase in the incidence of AAA [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although global mortality from AAAs is falling in both men and women, possibly related to decreased rates of smoking, women with AAAs still have lower survival compared with men with AAAs. 101 , 102 In a large 15-year national registry of 16,040 patients followed after elective endovascular aneurysm repair, 5-year survival was found to be significantly lower among White and Black women compared with White men (hazard ratio [HR], 1.2; 95% confidence interval [CI], 1.2-1.3 and HR, 1.4; 95% CI, 1.1-1.8, respectively). 103 Female sex has also been independently associated with significantly worse 30-day survival after elective repair after adjusting for repair type, age, aneurysm diameter, and comorbidities, but not aortic size index (odds ratio [OR],1.7; 95% CI, 1.1-2.6; P = 0.02).…”
Section: Sex Differences In Abdominal Aortic Diseasementioning
confidence: 99%